SISTEM INFORMASI E-RAPORT BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE (STUDI KASUS PADA SMPN 2 WAGIR KABUPATEN MALANG) - Asnawati Nona Erna Ngara; Wiji Setiyaningsih; Rini Agustina (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2023)
SMPN 2 Wagir School has used an excel-based desktop E-RAPORT. This system only covers about value processing. The process of entering values uses excel. Therefore, the author developed a website-based E-RAPORT system to facilitate the value processing process. The research uses the prototype model where this method is centered on presenting to users. The use of a systemized value processing application is able to cut the processing time of value data to be faster. The measurement of the feasibility level of the application was carried out by testing UAT (User Acceptence Test) which got very good results with an average percentage of 91% from 3 aspects of assessment.